Fatigue design of a twin internal combustion engine for a light helicopter by a CAE-based approach. Issue 6 (4th December 2017) - Gilioli, Andrea; Braconi, Dario; Guagliano, Mario
Abstract : Purpose: The purpose of this paper is to apply a computer-aided engineering approach in order to improve the performance and the reliability of an innovative internal combustion engine. The engine is called twin engine packs system and it consists into the presence of two independent piston engines working in the same crankcase, thus allowing the helicopter to meet the safety standards of the fail-safe design approach, as happens with the twin-turbine helicopters, but with reduced operative costs. The goal is to propose to the designers modifications aimed to improve the performance of the components. Design/methodology/approach: The crankshaft, connecting rod and the piston of the engine have been investigated by means of numerical FE models. Numerical fatigue assessments have been performed along with vibrational modes and buckling analysis in order to verify the structural integrity of the system. Findings: On the basis of the numerical results, some modifications have been proposed to the designers and the originally proposed geometry has been modified. Eventually, the mass of the engine has been reduced keeping a high reliability level. Practical implications: The prototype of the engine has been built following the modifications proposed in this paper. This paper represents a comprehensive application of a CAE methodology to a real industrial application. Originality/value: This paper shows a complete CAE procedure applied to a real working engine whose performances and reliability have been improved by following the findings of this paper.